2014
DOI: 10.2466/07.17.pr0.114k17w6
|View full text |Cite
|
Sign up to set email alerts
|

Forming Impressions: Effects of Facial Expression and Gender Stereotypes

Abstract: The present study of 138 participants explored how facial expressions and gender stereotypes influence impressions. It was predicted that images of smiling women would be evaluated more favorably on traits reflecting warmth, and that images of non-smiling men would be evaluated more favorably on traits reflecting competence. As predicted, smiling female faces were rated as more warm; however, contrary to prediction, perceived competence of male faces was not affected by facial expression. Participants' female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…negative, compared to neutral. The smiling results are supportive of findings by Hack (2014), which showed that participants rated smiling female faces more warmly than neutral female faces. These results are supportive of those reported by Senft et al (2016) study mentioned previously, which showed that smiling negated age and gender as inference inducers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…negative, compared to neutral. The smiling results are supportive of findings by Hack (2014), which showed that participants rated smiling female faces more warmly than neutral female faces. These results are supportive of those reported by Senft et al (2016) study mentioned previously, which showed that smiling negated age and gender as inference inducers.…”
Section: Discussionsupporting
confidence: 86%
“…These categories are used to make judgments about the perceived person, and the judgments are often stereotypical (Ebner et al, 2018;Ellemers, 2018;Lamont et al, 2015;Macrae and Bodenhausen, 2000). Research on age and gender perceptions indicates that these stereotypes are a mixture of positive and negative; for example, people over 65 are perceived as more Agreeable and less impulsive (positive), and less active and competent (negative; Chan et al, 2012;Hack, 2014). Females are perceived as more Agreeable, Conscientious and Open (positive), and sad (negative); and males are perceived as more Extraverted (positive), and angry and threatening (negative; Löckenhoff et al, 2014;Parmley and Cunningham, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study’s findings are in harmony with several researches showing that women are significantly more likely to smile in an inauthentic manner – as well as use these fake smiles to mask negative emotions – than men ( Prkachin and Silverman, 2002 ; LaFrance et al, 2003 ; Woodzicka, 2008 ). Despite these observations, facial expressions (enjoyment smiles, non-enjoyment smiles, and neutral expressions) from female players are generally perceived as more approachable ( Miles, 2009 ) and women may be perceived more favorably when smiling ( Hack, 2014 ). It is worth noting that women typically smile more often than men when social tension is high ( Hall and Halberstadt, 1986 ).…”
Section: Materials and Methods – Overviewmentioning
confidence: 98%
“…Other previous studies discussed the effect of facial gender on trustworthiness judgments ( Buchan et al, 2008 ), found that female faces were usually perceived as more trustworthy than male faces. It remains unclear, however, whether the processing of these two cues occurs independently ( Haxby et al, 2000 , 2002 ), or is simultaneously interactive ( Hess et al, 2000 ; Atkinson et al, 2005 ; Aguado et al, 2009 ; Ozono et al, 2010 ; Dong et al, 2014 ; Hack, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Experiment 2, we manipulated the social context on the basis of Experiment 1 to test if the effect of facial expression and facial gender would be influenced by context. Based on previous literature (e.g., Hack, 2014 ), we hypothesized that the effect of the cues were simultaneously interactive during trust judgments, and the effect of facial expression would be susceptible to social context, while the effect of facial gender would be stable in different settings.…”
Section: Introductionmentioning
confidence: 99%